In Vivo Interference of Rous Sarcoma Virus Budding by cis Expression of a WW Domain - Patnaik, Akash (American Society for Microbiology, 2002)
For all enveloped viruses, the actual mechanism by which nascent virus particles separate or “pinch off” from the cell surface is largely unknown. In the case of retroviruses, the Gag protein drives the budding process, and the virus release step is directed by the late (L) assembly domain within Gag. A PPPPY motif within the L domain of Rous sarcoma virus (RSV) was previously characterized as being critical for the release of virions and shown to interact in vitro with the WW domain of Yes-associated protein (Yap). To determine whether WW domain-L domain interactions can occur in vivo, we attempted to interfere with the host cell machinery normally recruited to the site of budding by inserting this WW domain in different locations within Gag. At a C-terminal location, the WW(Yap) domain had no effect on budding, suggesting that the intervening I domains (which provide the major region of Gag-Gag interaction) prevent its access to the L domain. When positioned on the other side of the I domains closer to the L domain, the WW(Yap) domain resulted in a dramatic interference of particle release, and confocal microscopy revealed a block to budding on the plasma membrane. Budding was restored by attachment of the heterologous L domain of human immunodeficiency virus type 1 Gag, which does not bind WW(Yap). These findings suggest that cis expression of WW domains can interfere with RSV particle release in vivo via specific, high-affinity interactions at the site of assembly on the plasma membrane, thus preventing host factor accessibility to the L domain and subsequent virus-cell separation. In addition, they suggest that L domain-specific host factors function after Gag proteins begin to interact.